Klotho prevents epithelial–mesenchymal transition through Egr-1 downregulation in diabetic kidney disease. Issue 1 (7th June 2021) - Li, Yang; Xue, Meng; Hu, Fang; Jia, Yijie; Zheng, Zongji; Yang, Yanlin; Liu, Xiaolian; Yang, Yuelian; Wang, Yanjing
Abstract : Introduction: As a key event leading to tubulointerstitial fibrosis in diabetic kidney disease (DKD), epithelial–mesenchymal transition (EMT) has drawn increasing attention from researchers. The antiaging protein Klotho attenuates renal fibrosis in part by inhibiting ERK1/2 signaling in DKD. Early growth response factor 1 (Egr-1), which is activated mainly by ERK1/2, has been shown to play an important role in EMT. However, whether Klotho prevents EMT by inhibiting ERK1/2-dependent Egr-1 expression in DKD is unclear.The aim of this study was to investigate whether Klotho prevents EMT through Egr-1 downregulation by inhibiting the ERK1/2 signaling pathway in DKD. Research design and methods: Male C57BL/6J mice fed an high-fat diet for 4 weeks received 120 mg/kg streptozotocin (STZ), which was injected intraperitoneally. Klotho and Egr-1 expression was detected in the renal cortices of these mice on their sacrifice at 6 and 12 weeks after STZ treatment. In In vitro studies, we incubated HK2 cells under high-glucose (HG) or transforming growth factor-β1 (TGF-β1) conditions to mimic DKD. We then transfected the cells with an Klotho-containing plasmid, Klotho small interfering RNA. Results: Klotho expression was significantly decreased in the renal cortices of mice with diabetes mellitus (DM) compared with the renal cortices of control mice at 6 weeks after treatment and even more significantly decreased at 12 weeks. In contrast, Egr-1 expression was significantly increased in mice with DM compared with control mice only at 12 weeks. We also found that Klotho overexpression downregulated Egr-1 expression and the (p-ERK1/2):(ERK1/2) ratio in HG-treated or TGF-β1-treated HK2 cells. Conversely, Klotho silencing upregulated Egr-1 expression and the (p-ERK1/2):(ERK1/2) ratio in HG-treated or TGF-β1-treated HK2 cells. Moreover, the effects of si-Klotho were abolished by the ERK1/2 inhibitor PD98059. Conclusions: Klotho prevents EMT during DKD progression, an effect that has been partially attributed to Egr-1 downregulation mediated by ERK1/2 signaling pathway inhibition.